Variability of cycle threshold values in an external quality assessment scheme for detection of the SARS-CoV-2 virus genome by RT-PCR - Buchta, Christoph; Görzer, Irene; Chiba, Peter; Camp, Jeremy V; Holzmann, Heidemarie; Puchhammer-Stöckl, Elisabeth; Mayerhofer, Maximilian; Müller, Mathias M; Aberle, Stephan W (Clinical chemistry and laboratory medicine, 2021)
The qualitative results of SARS-CoV-2 specific real-time reverse transcription (RT) PCR are used for initial diagnosis and follow-up of Covid-19 patients and asymptomatic virus carriers. However, clinical decision-making and health management policies often are based additionally on cycle threshold (C ) values (i.e., quantitative results) to guide patient care, segregation and discharge management of individuals testing positive. Therefore, an analysis of inter-protocol variability is needed to assess the comparability of the quantitative results. C values reported in a SARS-CoV-2 virus genome detection external quality assessment challenge were analyzed. Three positive and two negative samples were distributed to participating test laboratories. Qualitative results (positive/negative) and quantitative results (C values) were assessed. A total of 66 laboratories participated, contributing results from 101 distinct test systems and reporting C values for a total of 92 different protocols. In all three positive samples, the means of the C values for the -, -, -, -, and -genes varied by less than two cycles. However, 7.7% of reported results deviated by more than ±4.0 (maximum 18.0) cycles from the respective individual means. These larger deviations appear to be systematic errors. In an attempt to use PCR diagnostics beyond the identification of infected individuals, laboratories are frequently requested to report C values along with a qualitative result. This study highlights the limitations of interpreting C values from the various SARS-CoV genome detection protocols and suggests that standardization is necessary in the reporting of C values with respect to the target gene.